Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah dalam Penyelenggaraan Pemerintahan Daerah di Indonesia - Ansori, Mhd.; Isra, Saldi; Setiawan, Dian Bakti; Fahmi, Khairul (Wajah Hukum, 2024)
The Regional People's Representative Council which is the state institution that has undergone the most changes. This research aims to determine and analyze the Implementation of the Supervisory Function of the Regional People's Representative Council in the Implementation of Regional Government in Indonesia. This type of research is normative juridical. The results of the research are the supervisory function carried out by the Regional People's Representative Council towards the Regional Government in order to realize good governance so that it can achieve its goals. The Regional Representative Council must be able to correctly interpret the function and objectives of supervision, so that it can become an effective check & balance mechanism, optimize supervision so that it can have a positive influence as expected on the management of regional government, prepare the supervisory agenda for the Representative Council Regional People, Formulating standards, systems and standard procedures for supervision of the Regional People's Representative Council, as well as involving community participation in the supervision process. For this reason, it is recommended that there is a need for community participation in carrying out supervision so that the implementation of regional government policies can run well and it is necessary to develop supervision guidelines by the Regional People's Representative Council so that the supervision function can run more focused.